3D Printed Scaffolds Incorporated with Platelet‐Rich Plasma Show Enhanced Angiogenic Potential while not Inducing Fibrosis. (23rd November 2021) - Ibanez, Rita I. R.; do Amaral, Ronaldo J. F. C.; Simpson, Christopher R.; Casey, Sarah M.; Reis, Rui L.; Marques, Alexandra P.; Murphy, Ciara M.; O'Brien, Fergal J.
Abstract: Successful therapeutic strategies for wound healing rely on proper vascularization while inhibiting fibrosis. However, scaffolds designed for skin tissue engineering generally lack the biochemical cues that can enhance their vascularization without inducing fibrosis. Therefore, the objective of this work is to incorporate platelet‐rich plasma (PRP), a natural source of angiogenic growth factors, into a gelatin methacrylate (GelMA) hydrogel, yielding a bioink that can subsequently be used to 3D print a novel regenerative scaffold with defined architecture for skin wound healing. A PRP‐activated bioink is successfully 3D printed, and the resulting scaffolds present similar structural, rheological, and mechanical properties compared to GelMA‐only scaffolds. Furthermore, 3D printed PRP‐activated scaffolds facilitate controlled release of PRP‐derived growth factors for up to 14 days, presenting superior angiogenic potential in vitro (e.g., tubulogenesis assay) and in vivo (chick chorioallantoic membrane) compared to GelMA‐only scaffolds, while not inducing a myofibroblastic phenotype in fibroblasts (e.g., α‐smooth muscle actin expression). This disruptive technology offers the opportunity for a patient's autologous growth factors to be incorporated into a tailored 3D‐printed scaffold in theatre prior to implantation, as part of a single‐stage procedure, and has potential in other tissue engineering applications in which enhanced vascularization with limited fibrosis is desired. Abstract : Efficient vascularization and inhibiting fibrosis are particularly important for successful outcomes in wound healing. This study addresses both these issues through the incorporation of platelet‐rich plasma, a natural source of growth factors, into a gelatin methacrylate bioink with capability to be 3D printed into a novel implant. This technology has the potential to be used clinically as an autologous growth factor delivery system in a single‐stage surgical procedure.